Peningkatan Hasil Belajar Passing Bawah Dalam Permainan Bola Voli Melalui Metode Self Check Dan Audio Visual Pada Murid Sdn 13 Arfai Manokwari - Darmawan, Syamsul; Rusli, Muhammad (UNIVERSITAS NEGERI MAKASSSAR, 2019)
Efforts to Increase Outcomes of Learning Outcomes in Volleyball Games Through Self-Checking and Audio-Visual Methods for Students at SDN 13 Arfai Manokwari Regency. This study aims to find out: 1) To study the application of Self Check teaching methods and Audio Visual media, 2) To find out the results of applying the Self Check and Audio Visual teaching methods to fifth grade students of SDN 15 Arfai. This study uses a class action research method which was conducted in two cycles. The research instrument uses tests, observations and observations, data obtained according to the research subjects of students as many as 34 people. Based on the research results obtained from the research that passed below at the volleyball game using the Self-Examination method and the right Audio Visual Media planning, implementation in accordance with research and research procedures, resulting in increased student learning activities and outcomes. Based on the results of the study showed that the technique that passed the fifth grade students at SDN 13 Arfai in cycle 1 was 58.82% while in the second cycle it reached 100%. Thus, an indicator of the ability to pass under skills by 41.18%. Based on the results of this study it can be concluded that through the Self-Examination method and the Audio Visual media for the ability to pass below in class V students of SDN 15 Arfay provided a significant improvement.